Scepticism, evolution and conservatism in the thought of F.A. Hayek - Ebadi, Aref (2018)
This thesis examines the interrelationship between the concepts of evolution, scepticism and conservatism in the thought of Friedrich August von Hayek (1899-1992). It argues that the concept of evolution plays a vital role in Hayek’s epistemology and social philosophy. It proposes that Hayek’s understanding of the concept of evolution shaped his early writings on theoretical psychology and the formation of the mind. He subsequently developed his initial ideas in a more systematic way and discussed them in more depth in his writings on the epistemology and methodology of the social sciences. Hayek maintained that the underlying mechanism of the formation of mind and society is the mechanism of evolution. From Hayek’s point of view, the human mind and human society have simultaneously evolved through the process of evolution over millions of years. Hayek offered his evolutionary approach as an alternative to ‘constructive rationalism’. The thesis argues that Hayek’s evolutionary approach led him to adopt a scepticism about the role of reason in society. Hayek maintained that reason itself is the result of human civilization, a civilization that became possible due to rules and traditions that cannot be justified a priori. Hayek’s scepticism about the role and capacity of abstract reason and his emphasis on social institutions and traditions had placed his position close to conservatism. Although Hayek rejected any relation between his ideas and conservatism, this thesis tries to show why such a reading of Hayek’s political thought is plausible. After identifying three doctrines of conservatism, i.e. scepticism/pessimism, traditionalism and organicism, this thesis argues that there are some significant similarities between Hayek’s political thought and conservatism.